2022
DOI: 10.1002/ajh.26769
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of impaired antibody response after SARS‐CoV‐2 mRNA vaccination in hematopoietic cell transplant recipients: A Japanese multicenter observational study

Abstract: HCT recipients reportedly have a high mortality rate after developing COVID‐19. SARS‐CoV‐2 vaccination is generally useful to prevent COVID‐19. However, its safety and efficacy among HCT recipients remain elusive. This large‐scale prospective observational study including 543 HCT recipients with 37‐months interval from transplant demonstrated high safety profiles of mRNA vaccine: only 0.9% of patients avoided the second dose due to adverse event or GVHD aggravation following the first dose. Regarding the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The persistence of pre-cellular therapy SARS-CoV-2-specific humoral immunity was apparent based on the frequent presence of antibodies at the baseline time point in all cohorts, with generally higher antibody titers in patients tested earlier after cellular therapy. Notably, we did not observe associations with other clinical variables often considered in immunocompromised patients, such as the presence of GVHD, use of immunosuppressive therapies, or absolute lymphocyte counts (15)(16)(17)(18)(20)(21)(22)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The persistence of pre-cellular therapy SARS-CoV-2-specific humoral immunity was apparent based on the frequent presence of antibodies at the baseline time point in all cohorts, with generally higher antibody titers in patients tested earlier after cellular therapy. Notably, we did not observe associations with other clinical variables often considered in immunocompromised patients, such as the presence of GVHD, use of immunosuppressive therapies, or absolute lymphocyte counts (15)(16)(17)(18)(20)(21)(22)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 73%
“…Most studies focused on humoral immunity using binding antibody measurements, but evaluation of neutralizing antibodies and T cell responses provide additional data relevant to protection from severe infection (13,14). Studies in cellular therapy recipients have few participants vaccinated within the first 3-12 months, precluding conclusions about the optimal timing of vaccination after cellular therapy (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…The antibody response in allo-HCT recipients is influenced by various factors, including the number of CD19+ cells, the timeframe following transplantation, complete remission status, the use of immunosuppressive drugs, and the levels of lymphocyte subpopulations [25]. Recent studies have demonstrated the safety and efficacy of the primary cycle of the mRNA-based SARS-CoV-2 vaccine BNT162b2 in allo-HCT recipients, with approximately 50-80% of subjects generating a protective immune response [7,[26][27][28][29]. However, limited data are available regarding neutralizing antibody levels in allo-HCT recipients following SARS-CoV-2 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…After applying the eligibility criteria, 102 studies remained, forming the evidentiary basis for the guideline recommendations: 24 systematic reviews, 11, 14 RCTs, 6,[44][45][46][47][48][49][50][51][52][53][54][55][56] and 64 nonrandomized studies. [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120] The ...…”
Section: Characteristics Of Studies Identified In the Literature Searchmentioning
confidence: 99%